Transformation of Differential – Algebric Equations system to a system of differential equations using index reduction (Al-Mansour Journal, 2022)
In this paper, the system of differential – algebriaic equations has been transformed to a system of differential equations using index reduction , then the transformed systems was tested for stability by Sylvester's criterion depending on Liapunov functions .
Keywords: Sylvester's criterion; index reducation; semi – explicit differential algebraic equations